Review of Janet Afary and Kamran Afary MOLLĀ NASREDDIN The making of a modern trickster (1906–1911), Edinburgh: Edinburgh University Press, 2022. - Gezalova, Nigar Rovsan gyzy (History, Archeology and Ethnography of the Caucasus, 2023)
The legendary satirical magazine "Molla Nasreddin" was founded by the famous Azerbaijani educator and writer Jalil Mammadguluzade in 1906 and in a short time became a significant social and political event in the life of the countries of the Muslim East. Sharp satirical poems, articles and cartoons in a short time made the magazine the most popular publication, influencing the thinking of an entire generation. Reformation, the struggle against despotism, the struggle for the civil and political rights of women, education issues are only a small part of the problems raised in this first satirical magazine in the Middle East. The magazine also played an important role in the fact that in 1919 the Azerbaijan Democratic Republic was the first in the entire Muslim East to grant women the right to participate in elections. Despite strict censorship and prohibitions, the magazine continued to be published until 1931.